PENERAPAN METODE GAME BASED LEARNING DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITS SISWA MI MA'ARIF CANDIREJO - Rohmah, Siti (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
The research aims to overcome the problem of conventional learning methods that are less effective in attracting interest and increasing understanding of MI Ma’arif Candirejo students through the application of game based learning methods. Through a series of specially designed educational games, this research seeks to create a fun and interactive learning environment, so that it is expected to increase student motivation and involvement in the learning process. This activity involves students at MI Ma’arif Candirejo. Learning activities were carried out in three meetings with a focus on different educational games, including color concepts, types of lines, and basic mathematical operations. The result showed that the application of Game Based Learning was able to increase students’ enthusiasm, learning motivation, concept understanding, and participation in learning activities. Student reported higher enthusiasm and ease in understanding the learning materials. The homeroom teacher and principal also observed an increase in student engagement in the classroom.